Comparative Analysis of the Performance of the Sharia Stock Index (ISSI) and the Composite Stock Price Index (IHSG) Amid Economic Volatility 2020-2025 - La Ane, Rajab Ali; Sobar M Johari (Fast in Social Sciences, 2026)
This study aims to analyze and compare the performance of the Indonesia Sharia Stock Index (ISSI) and the Composite Stock Price Index (IHSG) in responding to economic volatility during the 2020–2025 period. This timeframe represents a phase of heightened economic uncertainty triggered by the COVID-19 pandemic, rising global inflation, monetary policy tightening, and international geopolitical instability, all of which exerted substantial pressure on Indonesia’s capital market. In this context, understanding the comparative characteristics and resilience of sharia and conventional stock indices is essential for both academic development and sustainable investment decision-making. This research adopts a qualitative approach using a literature review method. Data were collected through a systematic examination of reputable national and international academic journals, as well as official reports published by the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK). The analysis employs a descriptive-comparative framework by synthesizing empirical findings and theoretical perspectives related to stock index performance, market volatility, and the fundamental characteristics of sharia and conventional investments. The findings indicate that both ISSI and IHSG experienced significant fluctuations throughout the observation period, particularly during the early stage of the COVID-19 crisis. However, ISSI tended to exhibit relatively lower volatility compared to IHSG during periods of extreme economic pressure. This condition is associated with the sharia screening mechanism, which restricts interest-based leverage and speculative activities, resulting in a more defensive risk profile. Conversely, IHSG demonstrates greater sensitivity to macroeconomic changes and global investor sentiment, offering higher return potential under stable market conditions but accompanied by higher risk levels. The study concludes that ISSI shows stronger relative resilience during periods of high economic volatility, while IHSG performs more optimally in normal or expansionary market phases.